Analisis Mesin CNC Milling dengan Metode Overall Equipment Effectiveness dalam Mendeteksi Six Big Losses di PT. A - Eshardiansyah, Muhammad Carvin; Azizah, Fahriza Nurul; Wahyudin, Wahyudin (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
PT. A is a company engaged in the manufacturing industry with products produced in the form of (dies, jigs, and parts manufacturing). During the activity, the CNC milling machine Milltex Vex 580b experienced engine damage which resulted in the machine working unproductively and affecting the level of effectiveness of the CNC milling machine Milltex Vex 580b. Overall Equipment Effectiveness (OEE) is a method consisting of availability level, quality level, and performance level as a measurement of optimal machine performance tool productivity to maintain the effectiveness of a machine. To eliminate losses using Six Big Losses which are six big losses that can affect the level of machine effectiveness, the average OEE result is 69% where this result is still below world-class standards. This is due to losses caused by a reduction in loss speed of 42%. By analyzing the fishbone diagram (consequences) of this method, it can be concluded that the cause of the low effectiveness value in machine performance is due to the level of availability which is influenced by the reduction in loss speed.           Keywords: Effectiveness, Overall Equipment Effectiveness, Six Big Losses